2006
DOI: 10.1097/01.tp.0000229438.14914.82
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Evaluation of Pediatric Small Bowel Transplantation in the United Kingdom

Abstract: Firm conclusions on cost-effectiveness of SBTx are not possible given the two different estimates. The prognostic model approach (suggesting that pediatric SBTx may provide a small survival benefit at a small reduction in costs) should be less subject to bias, but the model requires external validation. Meanwhile, children at risk of fatal PN-complications should be given the opportunity to receive a SBTx only within a continuing formal assessment of the technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
(31 reference statements)
0
9
0
2
Order By: Relevance
“…In the 1989 study of Caniano and coworkers [8], the average cost of the initial hospitalization was $315,000-equivalent to €389,000 in 2006-with an average stay of 450 days in 10 patients. Recently, Longworth et al [27] showed that the average costs of 24 stable SBS patients (not requiring transplantation) were £159,000 based on 1998/1999 prices-equivalent to €266,000 in 2006-for 30 months, with a mean (SD) hospital stay of 50 (74) days. Finally, Spencer et al [28] calculated the treatment costs during the first 5 years after onset of SBS, including hospital care, outpatient care, and home care.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1989 study of Caniano and coworkers [8], the average cost of the initial hospitalization was $315,000-equivalent to €389,000 in 2006-with an average stay of 450 days in 10 patients. Recently, Longworth et al [27] showed that the average costs of 24 stable SBS patients (not requiring transplantation) were £159,000 based on 1998/1999 prices-equivalent to €266,000 in 2006-for 30 months, with a mean (SD) hospital stay of 50 (74) days. Finally, Spencer et al [28] calculated the treatment costs during the first 5 years after onset of SBS, including hospital care, outpatient care, and home care.…”
Section: Discussionmentioning
confidence: 99%
“…The cost-effectiveness of CSBLT versus long-term HPN is not clear,38 and is a somewhat artificial argument in light of donor organ shortage for the paediatric population. Local factors (high incidence of NEC) may contribute to our high use of HPN.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic study with a larger patient population (more than 100) is needed. Using a prognostic scoring system to identify costs, which would have been incurred by patients who were not transplanted, a review in the UK in 2006 concluded that small bowel transplantation in children was cost-effective (but with wide confidence intervals) [23]. Data about long-term cost-effectiveness from published data in the United States [11 ] suggest that ITx is a cost-effective alternative to parenteral nutrition -see summary in Table 2.…”
Section: Cost-effectivenessmentioning
confidence: 97%